2019
DOI: 10.1097/qad.0000000000002079
|View full text |Cite
|
Sign up to set email alerts
|

GlycA, a novel inflammatory marker, is associated with subclinical coronary disease

Abstract: CVD ancillary study, was involved in the CT data collection, and provided critical revisions to the paper. Dr. Budoff interpreted the cardiac CT scans for the study (CT Core Lab) and provided critical revisions to the paper. Dr. Otvos provided the GlycA measurements and provided critical revisions to the paper. Drs. Zhao, Brown, Guallar, Palella, Martinson, Akinkuolie, Haberlen, and Mora provided critical revisions to the paper. Dr. Michos, Fashanu, and Tibuakuu take full responsibility for its content. All au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…However, both the prevalence and incidence of DTAC (at 27% and 11%) was greater than the other 3 ECC markers, so there may be less statistical power to detect associations for the other ECC markers. Of note, DTAC has been shown to be associated with CAC 42 , and CAC has a positive association with GlycA 8 . Alternatively, there may be distinct biological mechanisms that lead to preferential calcification across the various vascular beds.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, both the prevalence and incidence of DTAC (at 27% and 11%) was greater than the other 3 ECC markers, so there may be less statistical power to detect associations for the other ECC markers. Of note, DTAC has been shown to be associated with CAC 42 , and CAC has a positive association with GlycA 8 . Alternatively, there may be distinct biological mechanisms that lead to preferential calcification across the various vascular beds.…”
Section: Discussionmentioning
confidence: 97%
“…Prior studies have examined the relationship between GlycA and subclinical coronary artery disease (CAD) as measured by CAC score on non-contrast CT or coronary plaque by coronary CT angiography. 8,31 In a case-control study involving patients with psoriasis, GlycA was found to be associated with subclinical CAD beyond ASCVD risk factors and hsCRP. 31 In another cross-sectional study conducted in patients with rheumatoid arthritis, GlycA was correlated with the presence of CAC and prevalent CAD.…”
Section: Discussionmentioning
confidence: 99%
“…4,[35][36][37][38][39] In several cross-sectional studies, there were strong positive associations between GlycA and coronary atherosclerosis among individuals with rheumatoid arthritis, 35 psoriasis, 40 and HIV infection. 20 In a study of participants undergoing cardiac catheterization, GlycA was strongly associated with the presence and extent of coronary artery disease and positively associated with cardiovascular and noncardiovascular mortality. 36 Similarly, a prospective cohort study found an association between baseline GlycA and incident CVD risk occurring over a median follow-up time of 17.2 years.…”
Section: Discussionmentioning
confidence: 99%
“…37 Several other studies have shown similar positive associations between GlycA and incident CVD, mortality, and cancer 4 and have shown that the relationship with CVD was stronger for GlycA than that reported for hsCRP 38 and is independent of hsCRP. 39 Despite the aforementioned established association of GlycA with incident CVD events 4 and with subclinical coronary and extra-coronary atherosclerosis, 20,21,40 the relationship of GlycA with subclinical and clinical PAD, specifically, had not been previously established. Although there are some common shared cardiovascular risk factors that promote atherosclerosis across various vascular beds, risk factors are not necessarily overlapping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation